Basic Beliefs About Wildlife and Migration: The Influence of the Prior State of Residence. Issue 1 (2nd January 2017) - Fix, Peter J.; Tracy, Quinn G.
ABSTRACT: This study compared mean scores on four items from the appropriate use basic belief dimension of the domination wildlife value orientation scale between life-long Alaska residents and migrants to Alaska from the western United States. Basic beliefs were compared among the migrant-sourcing states. Data were collected through a mail survey; 2, 264 questionnaires were completed (27% response rate) and 1, 673 responses were included in this analysis. When aggregated, migrants scored lower on the appropriate use basic beliefs than life-long Alaskans ( M  = 4.8 vs. 4.2), but no significant differences were found among the migrant-sourcing states. Among the migrants, length of time living in Alaska and education were predictors of basic belief scores. Although migrants might be exerting a slightly less utilitarian force on Alaska's dominant orientation toward wildlife, results also allow for the possibility that migrants with utilitarian-leaning views are choosing to move to Alaska.